Citrus Bioflavonoids Ameliorate Hyperoxaluria Induced Renal Injury and Calcium Oxalate Crystal Deposition in Wistar Rats - Sridharan Badrinathan; Micheal Thomas Shiju; Ramachandran Arya; Ganesh Nachiappa Rajesh; Pragasam Viswanathan (Tabriz University of Medical Sciences, 2015)
Purpose: Citrus is considered as a medically important plant from ancient times and the bioflavonoids of different variety of citrus fruits were well explored for their biological activities. The study aim was to explore the effect of citrus bioflavonoids (CB) to prevent and cure hyperoxaluria induced urolithiasis. Methods: Twenty four Wistar rats were segregated into 4 Groups. Group 1: Control; Group 2: Urolithic (EG-0.75%); Group 3: Preventive study (EG+CB, day 1-50); Group 4: Curative study (EG+CB, day 30-50). Animals received CB orally (20mg/kg body weight) after performing a toxicity study. Results: Urinary risk factors and serum renal function parameters were significantly reduced by CB administration in both preventive and curative study (p<0.001). Hematoxylin & Eosin and von Kossa staining demonstrated that renal protection was offered by CB against EG insult. Immunohistochemical analyses revealed over expression and abnormal localization of THP and NF-KB in urolithic rats, while it was effectively regulated by CB supplementation. Conclusions: CB prevented and significantly controlled lithogenic factors and CaOx deposition in rats. We propose CB as a potential therapy in management of urolithiasis.